Different Methods used to Control Early Blight of Potato in Laboratory Conditions - Ahmad, Salman; Aslam, Ayesha; Iqbal, Zafar; Ghazanfar, Muhammad Usman; Ahmad, Irfan; Ashraf, Ejaz; Atiq, Muhamad; Raza, Waqas; Anjum, Muhammad Zohaib; Asim, Muhammad (Asian Journal of Biological and Life Sciences, 2019)
The present study was designed with the objective “to assess the efficacy of various fungicides, salts and natural plant extracts with different doses against A. solani”. Results revealed that lowest mycelial growth and highest inhibition percentage of A. solani at highest concentration (2000 ppm) were observed in the fungicide treatments Bravo (2.2mm and 91%) followed by Dithane M-45 (3.65mm and 85.53%), Maneb-80 (7.55mm and 70%) while lowest was observed in case of Metalaxyl (11.29mm and 55.23%). Among inorganic salts, at the concentration of 5%, sodium bicarbonate inhibited maximum mycelial growth with maximum percentage inhibition (5.96mm and 77.82%) followed by potassium carbonate (9.1mm and 66.13%). In case of Plant extracts, P. hysterophorus was most effective to inhibit mycelia growth at the concentration 20%, while mycelial growth inhibition and inhibition percentage by P. hysterophorus at the concentrations of 10, 15 and 20% were (9.33mm and 56.26%), (11.58mm and 48.87%) and (10.53mm and 53%), respectively. Thus, the present study revealed that plant extracts and inorganic salts have shown significant inhibition and proved to be cost effective and eco-friendly for the management of A. solani and was comparable with fungicides.
Keywords: Blight; eco-friendly; Fungicide; Management; Plant extract; Potato